Investigation Of The Frequency Of Side Effects Of Inhaled Glucocorticosteroids From The Respiratory System In Children With Bronchial Asthma - Abulashova Madina Sirajutdinovna; Shaipova Aida Ibragimovna; Gadzhieva Khurzaday Khizirievna; Davudgadzhieva Aishat Mukhtarovna; Izieva Asiyat Makhachevna; Shangiraeva Patimat Shamkhalovna; Tagirova Amina Abubakarovna; Magomedkhabibov Mukhammad Magomedsalimovich; Azizova Karina Shakirovna; Kaialov Yakub Gazimagomedovich; Vagabova Shuainat Abdulaevna (Journal for ReAttach Therapy and Developmental Diversities, 2024)
Inhaled glucocorticosteroids, like other medications, have a number of side effects, one of which is candidiasis of the oropharynx. Objective: to study the frequency of infection of the pharynx with Candida fungi and to determine their sensitivity to antifungal drugs in children who have been using inhaled glucocorticosteroids for a long time. The main group included 65 patients. From the main group of the study, Candida fungi were found in 25 patients 38.5%± 6.78%. The sensitivity of Candida fungi to antifungal drugs was 100% to nystatin and clotrimazole, 96% to fluconazole.